Genetic diversity, heritability, and estimated breeding values for growth of domesticated Asian seabass Lates calcarifer from Thailand - Sirikan Prasertlux; Atra Chaimongkol; Jutaporn Chaimongkol; Sirithorn Janpoom; Sureerat Tang; Puttawan Rongmung; Wanwipa Ittarat; Parichart Ninwichian; Putth Songsangjinda; Takashi Sakamoto; Bavornlak Khamnamtong; Panya Sae-Lim; et al. (Aquaculture and Fisheries)
To establish a new breeding program, genetic diversity of five domesticated populations and two commercial stocks of Asian seabass (Lates calcarifer) were examined. Moderate levels of genetic diversity based on microsatellite polymorphism were found. The number of alleles per locus (NA) was 3.429–11.571. Observed (Ho) and expected (He) heterozygosities were 0.416–0.772 and 0.423–0.805. FST and genetic heterogeneity analysis revealed significant genetic differences of most pairwise comparisons (P < 0.001). Genetic distance between populations was 0.000–0.703. Phylogenetic analysis divided examined populations to two genetic stocks; A: DOF-Chachoengsao 2, DOF-Songkhla, and DOF-Trang and B: Commercial Farm 1 (Phuket) and Commercial Farm 2 (Chachengsao), DOF-Chachoengsao 1 and DOF-Krabi. The base population (G0, 51 families) was established from crosses between these founder populations. Heritability and estimated breeding values (EBVs) for growth in G0 families were evaluated at 519 day post hatch (dph, mean body weight = 616.64 ± 266.80 g, N = 1655). The heritability (h2) for growth of L. calcarifer in this study was 0.386 ± 0.020. The additive genetic coefficient of variation was 28% indicating high potential of genetic improvement for growth in this population. The distribution of EBVs showed high variation both between and within families. Fish exhibiting high EBVs (SATREPS-DOF-G0-hEBVs) clustered with a phylogenetic clade A while the SATREPS-DOF-G0-lEBVs group was phylogenetically allocated to clade B. Genetic selection with +1SD criteria is expected to achieve genetic gain of 28.5% per generation. The information on genetic diversity and EBVs estimates allows efficient implementation of our ongoing breeding program of L. calcarifer.